(4 + 3) Cycloaddition Reaction of Sulfonylphthalide with N,N '-Cyclic Azomethine Imines: Synthesis of Pyrimidinone-Fused Naphthoquinones - Sorabad, Ganesh Shivayogappa; Yang, Ding-Yah (Organic letters, 2023)
A base-mediated [4 + 3] cycloaddition reaction of sulfonylphthalide with , -cyclic azomethine imines to facilely synthesize novel pyrimidinone-fused naphthoquinones is described. The prepared compounds can be readily converted to isoquinoline-1,4-dione derivatives via alkaline methanolysis. Alternatively, the isoquinoline-1,4-dione can also be prepared by base-mediated one-pot three-component reaction of sulfonylphthalide with , -cyclic azomethine imines in methanol.